2018
DOI: 10.1039/c8cp04089c
|View full text |Cite
|
Sign up to set email alerts
|

Highly enhanced liquid flows via thermoosmotic effects in soft and charged nanochannels

Abstract: Enhancing nanoscale liquid flows remains an existing challenge in nanofluidics. Here we propose the generation of highly augmented thermoosmotic (TOS) liquid flows in soft nanochannels (or nanochannels functionalized by grafting with end-charged polyelectrolyte or PE brushes) by employing an axial temperature gradient. The TOS transport is a combination of the induced-electric-field electroosmotic (EOS) transport and a thermo-chemioosmotic (TCOS) transport with the latter resulting from an induced pressure gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 67 publications
1
16
1
Order By: Relevance
“…This study (Maheedhara et al 2018a) also showed enhanced transport, as the localization of the EOS body force is equally prevalent for the case with end-charged brushes. However, this study (Maheedhara et al 2018a) reported a less realistic flow field stemming from the fact that the brushes were modelled using the simplistic Alexander-de Gennes model (De Gennes 1976b;Alexander 1977), which in turn meant that the brushes had a uniform density distribution along their height leading to an over prediction of the brush-induced drag force (Sivasankar et al 2020a,b). On the other hand, this current paper that describes the brushes using an augmented SST considers a much more realistic monomer density distribution (having a much larger density at near-wall locations) and hence provides a more accurate description of the brush-induced drag force.…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations
“…This study (Maheedhara et al 2018a) also showed enhanced transport, as the localization of the EOS body force is equally prevalent for the case with end-charged brushes. However, this study (Maheedhara et al 2018a) reported a less realistic flow field stemming from the fact that the brushes were modelled using the simplistic Alexander-de Gennes model (De Gennes 1976b;Alexander 1977), which in turn meant that the brushes had a uniform density distribution along their height leading to an over prediction of the brush-induced drag force (Sivasankar et al 2020a,b). On the other hand, this current paper that describes the brushes using an augmented SST considers a much more realistic monomer density distribution (having a much larger density at near-wall locations) and hence provides a more accurate description of the brush-induced drag force.…”
Section: Introductionsupporting
confidence: 57%
“…the induced EOS flow). Over the past several years, such TOS transport in nanofluidic systems has been extensively studied (Dietzel & Hardt 2016, 2017 and has been identified to be useful in applications ranging from generating electricity in nanocellulose channels using waste heat (Li et al 2019), energy conversion and storage (Chen et al 2019), enhanced nanofluidic transport in presence of functionalization with PE brushes (Maheedhara et al 2018a), etc. For the past decade and a half, functionalizing nanochannels with PE brushes has been employed for applications such as analyte and biomolecule sensing (Ali et al 2011), fabrication of ionic nanofluidic diodes and current rectifiers (Ali et al 2009(Ali et al , 2013Yameen et al 2009Yameen et al , 2010Lin et al 2016), etc.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent set of papers, we made the first attempt to describe the ionic and liquid transport in PE brush–grafted nanochannels in a framework that accounts for the PE brush configuration while describing the PE brush EDL electrostatics . In other words, the PE brush EDL electrostatics is obtained by minimizing the free energy of the entire system that also yields the corresponding PE brush configuration.…”
Section: Introductionmentioning
confidence: 99%